Pertinent Today: What Contemporary Lessons Should be Taught by Studying Physician Participation in the Holocaust? - Levine, Mark A.; Wynia, Matthew K.; Himber, Meleah; Silvers, William S. (Conatus - Journal of Philosophy, 2019)
The participation of physicians in the atrocities of the Holocaust exposed vulnerabilities in medicine’s moral commitment to patients’ best interests that every health professional should recognize. Teaching about this history is challenging, as it is extremely complex and there are no common standards for what basic historical facts students in health professions training programs should learn. Nor is there guidance on how these historical facts can or should be related to contemporary ethical issues facing health professionals. To address these problems, we propose a set of core historical facts about health professional involvement in the Holocaust that every student in a health professional training program should learn. We then identify three ethical lessons from the Holocaust that are pertinent today as physicians struggle to maintain their moral compass and earn the trust of patients and the public: 1) The lesson of commitment to science; maintaining balance between reason and skepticism in the search for truth, (2) The lesson of clinical detachment; maintaining balance between necessary professional distance with a commitment to humanism and intimacy with patients, and 3) The lesson of competing loyalties; maintaining balance in upholding medicine’s multiple responsibilities, including to individual patients and the larger community. Embedding these facts and lessons into the education of health professionals is challenging yet critically important. Today’s physicians struggle with some of the same ethical tensions as did German physicians in the Nazi era, albeit in a much-attenuated fashion. Awareness of these tensions and taking active measures to maintain them in balance are necessary components of humanistic health care, which should be an integral part of health professional training programs.